2006
DOI: 10.1007/s00125-006-0412-3
|View full text |Cite
|
Sign up to set email alerts
|

The −374 T/A polymorphism in the gene encoding RAGE is associated with diabetic nephropathy and retinopathy in type 1 diabetic patients

Abstract: Aims/hypothesis The receptor for AGE (RAGE) is considered to be mainly an intracellular signal-transducer or pro-inflammatory peptide of possible importance for inflammation and autoimmune diseases. Our aim was to study whether the −374 T/A polymorphism in the gene encoding RAGE (AGER) is associated with diabetes type and presence of diabetic complications. Methods The AGER −374 T/A polymorphism was genotyped in 867 type 1 diabetic patients, 2,467 type 2 diabetic patients and 205 non-diabetic control subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 40 publications
1
54
2
Order By: Relevance
“…First, the AGER gene encoding RAGE has been associated with cardiovascular disease [2], proteinuria [2][3][4] and retinopathy [4] in patients with type 1 diabetes. Second, AGE-R1, which is encoded by DDOST, enhances the clearance of AGEs from the circulation [8], while diabetic nephropathy in patients with type 1 diabetes has been associated with low levels of AGE-R1 in circulating mononuclear cells and with elevated levels of serum AGEs [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the AGER gene encoding RAGE has been associated with cardiovascular disease [2], proteinuria [2][3][4] and retinopathy [4] in patients with type 1 diabetes. Second, AGE-R1, which is encoded by DDOST, enhances the clearance of AGEs from the circulation [8], while diabetic nephropathy in patients with type 1 diabetes has been associated with low levels of AGE-R1 in circulating mononuclear cells and with elevated levels of serum AGEs [9].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the functional single nucleotide polymorphism (SNP) −374T/A (rs1800624) in the promoter region of AGER is associated with cardiovascular disease in Finnish patients with type 1 diabetes and with proteinuria in patients with poor glycaemic control [2]. Subsequent studies have shown that AGER is associated with diabetic nephropathy in white patients with type 1 diabetes [3,4] and with sight-threatening diabetic retinopathy in type 1 diabetes patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…The class of S100A12 proteins consists of pro-inflammatory cytokines, mainly expressed by granulocytes, and are involved in the transduction of intercellular signalling events of Ca2+ [16], with a possible influence in the inflammatory process and in autoimmune diseases [76]. The AGEs and the S100/Calgranulins are those which have been most studied as agents of proinflammatory signalling [43,105] and which appear to trigger intercellular signalling mechanisms that could participate in some of the pathologies associated with diabetes, such as nephropathy [91], retinopathy [14], cardiovascular diseases [68] and loss of bone mass [42].…”
Section: Ages and Chronic Diabetic Complicationsmentioning
confidence: 99%
“…Association studies of RAGE polymorphisms with diabetes, cardiovascular disease and inflammatory diseases such as rheumatoid arthritis showed controversial results (Bucciarelli et al, 2002;Kankova et al, 2005;Lindholm et al, 2006;Bierhaus and Nawroth, 2009). …”
Section: Introductionmentioning
confidence: 99%